PROCESS OF INERTIZATION (DAMPENING) OF STEEL MAKING SLAG FOR ECONOMICAL REUSE - QUERES QUINDELER, JOAO; DE MENDONCA LASCOURT, RONALDO; PIMENTAL, JOAO, LUIZ; DE ALMEIDA MELO E SILVA, MARCOS, VALERIO; DE MENDONCA CARVALHO, MARCIO; DA SILVEIRA NOCI, OLIVEIRA (2005)
Is a process intended on reducing the volumetric expansion of steel slag through hydration and carbonation of the free magnesium and calcium oxides contained in the slag. The process is initiated with the preparation of a inertization yard, where the slag will be homogenously distributed until a previously defined thickness is achieved, being, later on, aerated and dampened, which will accelerate the hydration and carbonation chemical reactions on most of the free calcium and magnesium, which are the main responsible for the volumetric expansion of the steel slag, making the slag suitable for use in road works. La présente convention consiste à réduire le développement volumétrique de scories d'acier par hydratation et carbonation des oxydes de calcium et de magnésium libre contenus dans ces scories. Ce processus est initié avec la préparation d'une aire d'inertie, dans laquelle les scories seront réparties de manière homogène jusqu'à ce qu'une épaisseur définie préalablement soit obtenue, étant plus tard aérées et atténuées ce qui accélère les réactions chimiques d'hydratation et de carbonation sur la plupart du calcium et du magnésium libre, qui sont les principaux responsables du développement volumétrique des scories d'acier, ce qui rend ces scories utilisables dans des travaux routiers.